Primo Levi, the Hebrew Bible, and Dante’s “Commedia” in “Se Non Ora, Quando?” (Ticontre. Teoria Testo Traduzione, 2018)
Primo Levi’s 1982 novel Se Non Ora, Quando? is a fictional version of the partisan activity of Eastern European Jews during the Second World War. Through a deliberate set of allusions, echoes, and specific references to the Hebrew Bible and to Dante’s Commedia, Levi systematically turns his story of these humble Eastern European Jewish peasants, craftsmen, artisans, and other fellow travellers into epic heroes. He adapts the self-questioning and attempt at self-understanding of the Hebrew Bible to this contemporary story of loss of homeland and desire for a future home. By bringing this humanistic cultural legacy into the framework of a historical novel or fictionalized history, Levi resolves the dichotomy between history and literature to show how the western sacred and secular literary legacy provides the matrix to organize what on the surface appears as the random and cruel unfolding of history.  L'opera di di Primo Levi Se non ora, quando? (1982) è una versione romanzata dell'attività dei partigiani ebrei dell'Europa orientale durante la seconda guerra mondiale. Attraverso allusioni, echi, parallelismi e precisi riferimenti alla Bibbia ebraica e alla Commedia di Dante, Levi trasforma sistematicamente in una narrazione eroica la storia di questi contadini e artigiani, ebrei dell’Europa orientale, e dei loro compagni di viaggio. Adatta l'esame personale e il tentativo di autocomprensione della Bibbia ebraica in questa storia contemporanea di perdita della patria e di desiderio di una futura casa. Inserendo questo lascito culturale umanistico nel quadro di un romanzo storico o di un resoconto storico romanzato, Levi trasforma la storia in letteratura mentre usa l’eredità letteraria occidentale sia sacra sia profana per fornire una matrice per organizzare ciò che sulla superficie appare come lo svolgimento casuale e crudele della storia. PAROLE CHIAVEHebrew Bible; Dante; Exile; Eastern European Jews; Partisans; Se Non Ora, Quando?; History and fiction.